STUDENTS’ MOTIVATION AND ITS IMPACT ON ENGLISH LANGUAGE LEARNING SUCCESS - Tursunboyeva O’g’iloy; Marhabo Shokirova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Students’ motivation is a critical determinant of success in English language learning. Motivation influences learners’ effort, persistence, and engagement, shaping academic achievement and communicative competence. Research indicates that both intrinsic and extrinsic factors contribute to language acquisition outcomes, with higher motivation levels correlating with improved proficiency and test performance. This study synthesizes theoretical constructs and empirical evidence on motivational types, contextual influences, and pedagogical strategies, underlining the role of educators in fostering sustained motivation.